Computational Thinking and Career Identity Among Electrical Engineering Students - L Endah Cahya Ningrum; Tuwoso Tuwoso (Indonesian Journal Publisher, 2026)
In the digital transformation era, computational thinking is vital in engineering education, yet its integrated role in shaping electrical engineering students’ career identity remains underexplored. This study aims to analyse the conceptual relationship between computational thinking and the career identity of electrical engineering students within the context of engineering higher education. The study employed a structured narrative review of 31 reputable international journal articles indexed in Scopus and Web of Science, published between 2022-2026. The analysis was conducted thematically through data reduction, open coding, theme categorisation, and narrative synthesis to identify patterns of relationship among computational thinking, career identity, and psychosocial linking factors. The findings indicate that computational thinking should not be positioned merely as a learning outcome, but rather as an epistemic-professional resource that has the potential to strengthen the career identity of electrical engineering students. This relationship does not occur directly; instead, it is mediated by self-concept, sense of belonging, and career aspirations. This review proposes a conceptual model in which engineering learning experiences foster the development of computational thinking, which subsequently strengthens students’ perceptions of competence and academic meaningfulness, thereby contributing to the formation of career identity. These findings extend the existing literature by integrating computational thinking, engineering identity, and psychosocial factors into a unified framework that is relevant to electrical engineering education.